Peran Kepolisian dalam Pemenuhan Hak Korban Perdagangan Orang - Abdelnoer, Muhammad Syaddam; Shafira, Maya; Tamza, Fristia Berdian; Farid, Muhammad; Meidiantama, Refi (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
Human trafficking is a serious crime that violates human dignity and fundamental human rights and is often categorized as a form of modern slavery. Victims of human trafficking experience multidimensional suffering, including physical, psychological, social, and economic harm, which requires comprehensive legal protection from the state. This study aims to analyze the role of the police in fulfilling the rights of victims of human trafficking and to identify the obstacles encountered in the implementation of such protection. The research employs a normative-empirical legal research method. The normative approach examines laws and regulations related to the protection of victims of human trafficking, while the empirical approach analyzes their implementation in practice, particularly within the jurisdiction of the Lampung Regional Police. The results show that the police play a strategic role in identifying and rescuing victims, providing physical and psychological protection, facilitating access to justice, and coordinating with relevant institutions for victim rehabilitation. However, the fulfillment of victims’ rights has not been fully optimized due to several obstacles, including limited human resources, inadequate facilities, weak inter-agency coordination, economic vulnerability of victims, and social stigma. Therefore, strengthening victim-oriented policing, improving institutional capacity, and enhancing cross-sectoral cooperation are essential to ensure effective and just protection for victims of human trafficking.